PENGARUH DISIPLIN KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT RAMAYANA LESTARI SENTOSA DI BATAM - Lyanzha, Helcho Guswa; Mardika, Nanda Harry (SCIENTIA JOURNAL, 2021)
This study aims to examine the influence of Work Discipline and Competence on the performance of employees of PT Ramayana Lestari Sentosa in Batam. This research uses a quantitative approach and nonprobability sampling techniques with a saturated sampling method. The data collection technique used a questionnaire with a Likert scale which was filled in by 103 respondents. Data were analyzed using SPSS version 25. The test results for the work discipline variable were t count 9.619> t table 1.98397 and sig t 0.000 <α 0.05. The result of the competency variable test is t count 4.719> t table 1.98397 and sig t 0.000 <α 0.05. The results of the f test are f count 201.661> f table 3.09 and a significance of 0.000 <alpha 0.05, it can be concluded that work discipline and competence partially and simultaneously have a significant effect on the performance of employees of PT Ramayana Lestari Sentosa in Batam. The test results of the coefficient of determination have a value of 0.801, which means that 80.1% of variations in employee performance variables can be explained by work discipline and competency variables, the remaining 19.9% ​​is explained by variables not examined in this study.